-
If a + 1 = √3 ,then the value
of a18 + a12 + a6 + 1 isa
-
- 0
- 1
- – 1
- 4
- 0
Correct Option: A
Using Rule 1 and 8,
a + | = √3 | |
a |
On squaring both sides ,
⇒ a2 + | + 2 = 3 | |
a2 |
⇒ a2 + | = 3 – 2 = 1 | |
a2 |
On cubing both sides,
⇒ | ![]() | a2 + | ![]() | 3 | = (1)3 | |
a2 |
⇒ a6 + | + 3 | ![]() | a2 + | ![]() | = 1 | ||
a6 | a2 |
⇒ a6 + | = 1 - 3 = -2 | |
a6 |
⇒ | = -2 | |
a6 |
⇒ a12 + 2a6 + 1 = 0
⇒ ( a6 + 1 )2 = 0
⇒ a6 + 1 = 0
∴ Expression = a18 + a12 + a6 + 1
Expression = a12(a6 + 1) + 1(a6 + 1) = 0